Training comprehensiveness: construct development and relation with role behaviour. Issue 7 (3rd August 2015) - Srivastava, Anugamini Priya; Dhar, Rajib Lochan
Abstract : Purpose: – This study aims to develop the scale for perception of training comprehensiveness and attempts to examine the influence of perception of training comprehensiveness on role behaviour: teachers' efficacy as a mediator and job autonomy as a moderator. Design/methodology/approach: – Through the steps for a generation, refinement, purification and validation of the scale, the measures of training comprehensiveness are defined, followed by an exploratory factor analysis. In all, 961 primary school teachers and 323 principals participated in the study. Teachers rated their perception of training comprehensiveness, self-efficacy and job autonomy, while principals rated the role behaviour of teachers, to avoid self-reporting biases. Findings: – Regression analysis showed that training comprehensiveness affects teachers' self-efficacy, higher teachers' efficacy increases the teachers' role behaviour, training comprehensiveness indirectly influences role behaviour and job autonomy moderated the channel of teachers' efficacy and role behaviour. These results indicated that in primary schools specifically in rural areas of India, individual perception of training, skill development and human resource development practice induces teachers' role behaviour via raising their efficacy to combat with adverse situations. Job autonomy on an independent basis moderates the positive relationship between self-efficacy and role behaviour. Practical implications: – This study also provides various practical and research-based implications. Originality/value: – The scale for training comprehensiveness has been developed, and its impact on behavioural attributes like efficacy and role behaviour is examined for a sample of teachers.